The Ninth Intersociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems (IEEE Cat. No.04CH37543)
DOI: 10.1109/itherm.2004.1319156
|View full text |Cite
|
Sign up to set email alerts
|

Thickness measurements of the thin film in spray evaporative cooling

Abstract: With electronic circuits becoming increasingly powefil, the limiting factor in their design is frequently related to thermal management. Spray evaporative cooling (SEC) has the capability to remove very high heat fluxes with a low fluid flow rate and can be packaged in a compact design. In order to allow M h e r development of SEC, fundamental mechanisms of heat removal must be understood. One important mechanism is conduction through the thin, two-phase film that develops on the surface. This paper presents m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Another complication to understanding the spray-cooling heat transfer mechanism is the small scales at which these phenomena occur. For example, the thin liquid film in which the nucleation takes place and heat is transferred had been measured to be anywhere from 1 to 350 m (Pautsch et al [9]). Measurement of temperature and visualization of liquid-vapor-interface dynamics in such small thicknesses in which heat transfer and phase change occur during spray experimentation are very difficult.…”
Section: Doi: 102514/134982mentioning
confidence: 99%
See 1 more Smart Citation
“…Another complication to understanding the spray-cooling heat transfer mechanism is the small scales at which these phenomena occur. For example, the thin liquid film in which the nucleation takes place and heat is transferred had been measured to be anywhere from 1 to 350 m (Pautsch et al [9]). Measurement of temperature and visualization of liquid-vapor-interface dynamics in such small thicknesses in which heat transfer and phase change occur during spray experimentation are very difficult.…”
Section: Doi: 102514/134982mentioning
confidence: 99%
“…When a droplet (i.e., the cold liquid) impacts and mixes with the liquid over the hot surface for each thermal layer, due to the impact, some amount of cold liquid starts moving upward and some moves toward the hot surface (as shown in Figs. [7][8][9]. Because the density of the vapor is lower, the vapor bubble also tries to move upward.…”
Section: A Effect Of Thermal-boundary-layer Thicknessmentioning
confidence: 99%
“…The film thickness may be the most important but one of the least studied parameters. The film thickness must be known in order to calculate the fluid velocity, the conduction rate, the nucleation size, as well as other important parameters [13].…”
Section: Review Of Film Thickness and Temperaturementioning
confidence: 99%
“…However, the variations in the film thickness and the film temperature are sometimes contradicted to each other. For example, Yang et al [14,15] concluded that the variation in the film thickness was less than 1µm in the spray impact area under their study, and Tilton et al [14,16] also assumed that the film had a uniform thickness under the spray, while Pautsch [13,14] measured the film thickness using an optical method involving total internal reflection, the film thickness measurements were compared with a numerical model of the film, the results indicated that the thinnest film is in the region under the orifice and the thickest is at the corner. Some discussions about the temperature variation observed in the liquid film on a spray cooled surface are as follows: Gu et al [17,18] found that spray cooling resulted in a relatively uniform temperature distribution over the heater surface, while Shedd and Pautsch [17,19] found quite significant temperature variation over their test heater reaching as high as 17°C.…”
Section: Review Of Film Thickness and Temperaturementioning
confidence: 99%
“…Pautsch et al (2004) have reported spray impingement cooling liquid film thicknesses ranging between 80 jim and 300 jim. The assumed liquid film thickness in the region of droplet impact (1.5 jim) has then been computed based on the assumed value of the crater diameter (250 gim), and assuming no splashing.…”
mentioning
confidence: 99%